Relationship between body mass index and simple visual reaction time in students of a medical college of Nepal - Bhat, Neeti; Mahotra, Narayan Bahadur; Shrestha, Lava; Aryal, Vibina; Rayamajhi, Nirmala; Gurung, Sanyukta (Journal of Physiological Society of Nepal, 2020)
Introduction: Obesity is a chronic condition with an increase in adipose tissues. It is known to affect various systems of body including the central nervous system. Reaction time is a measure of the integrity of the central nervous system which is an integrated voluntary response to a stimulus that includes receiving and processing of stimulus, drawing inference, and generating a motor response. This study was conducted with the objective of finding a relationship between body mass index, a measure of obesity and simple visual reaction time. Materials and methods: This cross-sectional analytical study was conducted on 60 participants aged 18-25 years. The body mass index of participants was calculated using Quetelet’s index, calculated by weight in kilograms divided by square of height in meter. Deary-Liewald reaction time task software version 3.10 was used to analyze their simple visual reaction time. Correlation of reaction time and body mass index was assessed using Pearson’s correlation test. Results: A weak positive correlation (r= 0.17) was observed between body mass index and simple visual reaction time but the correlation coefficient was not statistically significant (p=0.19). Conclusions: Slower visual reaction time with an increase in body mass index was noted. But the findings of current study were inadequate to deduce if any linear relationship exists between simple visual reaction time and body mass index.